Theoretical kinetics study of the reactions CHClBr + HBr ⇄ CH2ClBr + Br, CCl2Br + HBr ⇄ CHCl2Br + Br and CClBr2 + HBr ⇄ CHClBr2 + Br - Bracco, Larisa Laura Beatriz (2018)
The kinetics of CHClBr + HBr ⇄ CH2ClBr + Br (1, -1), CCl2Br + HBr ⇄ CHCl2Br + Br (2, -2) and CClBr2 + HBr ⇄ CHClBr2 + Br (3, -3) reactions at 293–787 K has been studied by using the canonical transition state theory with molecular information provided by different quantum chemical methods. The obtained rate constants (in cm3 molecule−1 s−1) are k1 = 5.24 × 10−13 exp[−1.47 kcal mol−1/RT], k−1 = 2.70 × 10−11 exp[−10.21 kcal mol−1/RT], k2 = 4.18 × 10−13 exp[−2.49 kcal mol−1/RT], k−2 = 6.96 × 10−12 exp[−7.36 kcal mol−1/RT], k3 = 3.29 × 10−13 exp[−2.20 kcal mol−1/RT], and k−3 = 8.45 × 10−13 exp[−7.10 kcal mol−1/RT]. Rate constants for (2, -2) and (3, -3) are here reported for the first time.